Effects of Approach-Avoidance Training on Implicit and Explicit Evaluations of Neutral, Angry, and Smiling Face Stimuli. Issue 1 (August 2013) - Woud, Marcella L.; Becker, Eni S.; Lange, Wolf-Gero; Rinck, Mike
A growing body of evidence shows that the prolonged execution of approach movements towards stimuli and avoidance movements away from them affects their evaluation. However, there has been no systematic investigation of such training effects. Therefore, the present study compared approach-avoidance training effects on various valenced representations of one neutral (Experiment 1, N = 85), angry (Experiment 2, N = 87), or smiling facial expressions (Experiment 3, N = 89). The face stimuli were shown on a computer screen, and by means of a joystick, participants pulled half of the faces closer (positive approach movement), and pushed the other half away (negative avoidance movement). Only implicit evaluations of neutral-expression were affected by the training procedure. The boundary conditions of such approach-avoidance training effects are discussed.